Alterations in Faecal Metagenomics and Serum Metabolomics Indicate Management Strategies for Patients With Budd-Chiari Syndrome - Lu, Qinwei; Xu, Hao; Zhou, Lin; Zhang, Ruifang; Li, Zhen; Xu, Peng; Bai, Tao; Wang, Zhiwei; Wu, Gang; Ren, Jianzhuang; Jiao, Dechao; Song, Yan; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
We investigated the effects of gut microbiota and serum metabolite levels in patients with Budd-Chiari syndrome (B-CS) and their importance for guiding clinical management strategies. In total, 214 B-CS patients (93 untreated and 121 treated) and 41 healthy controls were enrolled. Gut microbiota and serum metabolome were analysed using shotgun metagenomics and liquid chromatography-mass spectrometry. The gut microbiota of the patients showed abundance of Campylobacter and low levels of Saccharomyces, Deinococcus, and Thiomonas (P < 0.05). Thirty metabolites, including taurocholate and (R)-3-hydroxybutyric acid, were identified in the patients (VIP > 1, P < 0.05 and FC > 1.2 or FC < 0.83). Random forest (RF) models showed that serum metabolome could effectively identify B-CS from healthy controls and RF-metabolomics exhibited perfect discrimination (AUC = 100%, 95% CI: 100% – 100%), which was significantly higher than that achieved by RF-metagenomics (AUC = 58.48%, 95% CI: 38.46% – 78.5%). Campylobacter concisus and taurocholate showed significant positive correlation in patients with clinical manifestations (P < 0.05). Actinobacteria levels were significantly higher in untreated patients than in treated patients (P < 0.05). Campylobacter and Veillonella levels were significantly higher in treated patients than in healthy controls (P < 0.05). We identified major alterations in the gut microbiota and serum metabolome of patients with B-CS. Faecal metagenomics- and serum metabolomics-guided management strategies are required for patients with B-CS.